2022
DOI: 10.1177/10711007221088821
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Gait Simulation of the Effect of Subtalar Arthrodesis on Total Ankle Replacement Kinematics

Abstract: Background: Patients undergoing total ankle replacement (TAR) often have symptomatic adjacent joint arthritis and deformity. Subtalar arthrodesis can effectively address a degenerative and/or malaligned hindfoot, but there is concern that it places abnormal stresses on the TAR and adjacent joints of the foot, potentially leading to early TAR failure. This study hypothesized that ankle and talonavicular joint kinematics would be altered after subtalar arthrodesis in the setting of TAR. Methods: Thirteen mid-tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…18 The use of 14 specimens was based on previous studies reporting joint kinematics. 3,12 The sample size was chosen to have sufficient power to compare the single and double arthrodeses conditions to intact (repeated measures), to compare single to double hindfoot arthrodeses (repeated measures), and to assess the differences between the ST double and TN double arthrodesis groups (2 independent groups).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The use of 14 specimens was based on previous studies reporting joint kinematics. 3,12 The sample size was chosen to have sufficient power to compare the single and double arthrodeses conditions to intact (repeated measures), to compare single to double hindfoot arthrodeses (repeated measures), and to assess the differences between the ST double and TN double arthrodesis groups (2 independent groups).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results align with previous biomechanical evidence indicating that a subsequent subtalar arthrodesis after TAA can alter tibiotalar motion. 1,12 One study assessing the impact on post-TAA kinematics of subtalar arthrodesis observed increased tibiotalar internal rotation during the late stance. 12 Our results also showed an increased internal tibiotalar joint rotation following double hindfoot arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UMS was a robot with six degrees of freedom, four linear tendon actuators, and a rotatory Achilles actuator to simulate muscle engagement during walking. Lastly, a 2022 study used a robotic gait simulator to measure osseous kinematics after subtalar arthrodesis in cadavers with TAA implants, ultimately finding that ankle kinematics at the talonavicular joint were significantly altered after subtalar arthrodesis, correlating to clinical observations that have indicated that subtalar arthrodesis may be a risk factor for TAA failure [ 21 ]. Multiple other studies have also performed similar in vitro studies of foot bone and ligamentous kinematics with custom cadaveric gait simulators [ 22 , 23 , 24 ], with recent studies utilizing them to examine progressive collapsing foot deformities to best simulate stance phase and characterize the foot pathology [ 21 ].…”
Section: Translational/preclinical Reviewmentioning
confidence: 99%
“…Lastly, a 2022 study used a robotic gait simulator to measure osseous kinematics after subtalar arthrodesis in cadavers with TAA implants, ultimately finding that ankle kinematics at the talonavicular joint were significantly altered after subtalar arthrodesis, correlating to clinical observations that have indicated that subtalar arthrodesis may be a risk factor for TAA failure [ 21 ]. Multiple other studies have also performed similar in vitro studies of foot bone and ligamentous kinematics with custom cadaveric gait simulators [ 22 , 23 , 24 ], with recent studies utilizing them to examine progressive collapsing foot deformities to best simulate stance phase and characterize the foot pathology [ 21 ]. When comparing the range of motion of joint rotations and translations with the gold standard for in vivo kinematics, each of these studies demonstrated replicability and correspondence with in vivo values, suggesting the advantage of robotic gait simulators for providing exceptionally realistic descriptions of bony and ligamentous motion.…”
Section: Translational/preclinical Reviewmentioning
confidence: 99%